2016
DOI: 10.20944/preprints201611.0049.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vitamin-D Deficiency Predicts Infections in Young North Indian Children: A Secondary Data Analysis

Abstract: Recent studies have demonstrated a relationship between poor vitamin D status and respiratory infections and diarrhea among young children. Acute lower respiratory infections (ALRI) and diarrhea are among the two most important causes of death in under-5 children. In this analysis, we examine the extent to which vitamin-D deficiency (<10 ng/ml) predicts these outcomes using data from a randomized controlled trial (RCT) of daily folic acid and/ or vitamin B12 supplementation for six months in 6 to 30 months old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
3
1
Order By: Relevance
“…involving children 3 months-12 years of age showed that 40.25% of children were Vitamin D deficient (<20 ng/ml) which was lower than our reported prevalence [20]. In contrast, two studies from Delhi reported lower prevalence of Vitamin D deficiency than our study [21,22]. A study by Ray et al enrolled 72 infants aged 9-10 months who were term healthy and breastfed till 6 months.…”
Section: Vol 7 | Issue 12 | December 2020contrasting
confidence: 80%
See 1 more Smart Citation
“…involving children 3 months-12 years of age showed that 40.25% of children were Vitamin D deficient (<20 ng/ml) which was lower than our reported prevalence [20]. In contrast, two studies from Delhi reported lower prevalence of Vitamin D deficiency than our study [21,22]. A study by Ray et al enrolled 72 infants aged 9-10 months who were term healthy and breastfed till 6 months.…”
Section: Vol 7 | Issue 12 | December 2020contrasting
confidence: 80%
“…Vitamin D deficiency (<20 ng/ml) was observed only in 34.7% of infants [21]. Similarly, a study by Chowdhury et al among 6-30 months old infants from New Delhi, the prevalence of Vitamin D deficiency (<10 ng/ml) was seen in 34.5% of cases which is again lower than the 45.2% observed in our study [22]. The prevalence of Vitamin D deficiency in current literature is marked by variability of underlying cutoff values and analytical methods used for the assessment of Vitamin D levels making it difficult to make direct comparisons between studies [10,23,24].…”
Section: Vol 7 | Issue 12 | December 2020supporting
confidence: 50%
“…Some of studies reported the association between vitamin D level and viral infections. A study evaluating Indian children found that acute lower respiratory infection was significantly higher among children with vitamin-D deficiency in a six-month follw-up time (22). Banajeh investigated 79 cases between 2-59 months and found that vitamin D deficiency was associated with reduced circulating neutrophils and hypoxemia (23).…”
Section: Discussionmentioning
confidence: 99%
“…Being underweight, which was also found in our analysis, is one of the risk factors. Other factors include deficiencies of micronutrients such as vitamin D and Zn (27)(28)(29) that are common in severely malnourished children.…”
Section: Discussionmentioning
confidence: 99%